Respuesta :

jan56

It would be 200 because if you plug in -2 into the (x) as in replacing it, you get an answer that answer then goes to g(x) and replace that too. Hope you understand :)

We want to find the composition of the two given functions, we will have:

g(f(2)) = 8

So we have two functions:

f(x) = 3x - 8

g(x) = x² + 4

We want to get g(f (-2)), so first let's get g(f(x)), this means that instead of x in g(x) we evaluate it in f(x), we will get:

g(f(x)) = f(x)² + 4

Now replace f(x) by the function:

g(f(x)) = (3x - 8)² + 4

Now we evaluate it in x = 2:

g(f(2)) = (3*2 - 8)^2 + 4 = (-2)² + 4 = 8

g(f(2)) = 8

If you want to learn more, you can read:

https://brainly.com/question/5614233